Tinjauan Penerapan Rekam Medis Elektronik di Pendaftaran Rawat Jalan RSUD Balaraja - Bella Safitri; Noor Yulia; Lily Widjaja; Bangga Agung Satrya (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
The implementation of Electronic Medical Records (EMR) is a digitalization innovation in medical data storage which aims to increase the efficiency of health services. At Balaraja Regional Hospital, the EMR system is implemented using the Hospital Information Management application (MIRSA). This study aims to evaluate the implementation of EMR in outpatient registration, identify the obstacles faced, and provide recommendations for improvement. The scope of the research includes an outpatient registration system that uses EMR. Descriptive research method with qualitative analysis, by means of observation and interviews with the main informant, the head of medical records and other informants, registration officers. The research results show that the implementation of EMR has increased service efficiency by speeding up the registration process and reducing manual recording errors. However, analysis using the Human, Organization, Technology, Net-Benefit (HOT-Fit) method revealed obstacles such as technological aspects and organizational support, as well as slow network constraints. The conclusion of this research is that although EMR provides benefits in increasing service efficiency, improvements are still needed in technological and management aspects. It is recommended that Balaraja Regional Hospital develop special SOPs for MIRSA, improve system maintenance, and provide regular training officers to improve the quality of health services.